Cambodia's Second Kingdom : Nation, Imagination, and Democracy - Baker, Christopher John, 1948-; Baker, Christopher John, 1948-; Pasuk Phongpaichit; Pasuk Phongpaichit (Book collections on Project MUSE., 2016)
This book contains the first academic translations of key legal texts from the Ayutthaya era (1351-1767), along with an essay on the role of law in Thai history. The legal history of Southeast Asia has languished because few texts are accessible in translation. The Three Seals Code is a collection of Thai legal manuscripts surviving from the Ayutthaya era. The Palace Law, probably dating to the late fifteenth century, was the principal law on kingship and government. The Thammasat, a descendant of India's dharmasastra, stood at the head of the Code and gave it authority. Here these two key laws are presented in English translation for the first time along with detailed annotations and analyses of their content --Back cover.